Problematika Implementasi Pembelajaran Bahasa Arab Kurikulum Merdeka: Studi kasus: Kelas XI di SMA Al-Ashriyyah Nurul Iman Parung Bogor - Sidik, Alan Muhamad Taofik Maulana; Isyanto, Nur; Parhan, Parhan; Jalil, Muhammad Abdul` (STAINI Press, 2024)
This research uses a qualitative approach which discusses the problems that occur at Al-Ashriyyah Nurul Iman Parung Bogor High School in the Problems of Implementing Arabic Language Learning in the Merdeka Curriculum for Class XI. The Merdeka Curriculum is a new curriculum which has been implemented as a refinement of the previous curriculum, namely the 2013 curriculum. In its implementation in learning, the Merdeka Curriculum has been developed into a more variable curriculum but still focuses on basic materials, character development and competence in students. As stated in the review, the independent curriculum aims to restore the learning crisis which is getting worse due to the pandemic. Apart from that, it also aims to provide freedom to institutions and teachers to develop and manage curriculum and learning that is adapted to the characteristics of educational units and students. This research took several respondents consisting of school principals, Head of Curriculum, Arabic Language Teachers and several students who were thought to be capable and understood this research. In collecting data, interview techniques, field observations and documentation were used. The results of this research state that there are several problems, namelychanging old thought patterns or habits in teaching, lack of detailed understanding regarding differentiated learning, lack of up-to-date information, students' understanding of the implementation of Independent Curriculum Arabic Language Learning, lack of facilities that support the Independent Curriculum Arabic Language Learning Implementation project, the number of students is very diverse